Institutionalization of ethnochoreology in Serbia: The legacy of Ljubica Janković at the Institute of musicology SASA - Dumnić Marija; Lajić-Mihajlović Danka (Muzikologija, 2014)
Since 1964, the Institute of Musicology of the Serbian Academy of Sciences and Arts has been cherishing the official archive of the academician Ljubica Janković, ethnochoreologist, which originates from her service at the Ethnographic Museum in Belgrade (1939-1951). The legacy contains documentation about the activity of the Folk Dance Section of the Ethnographic Museum in Belgrade, and extensive data on folk dances in Yugoslavia from the first half of the twentieth century. This paper presents part of the archival documentation relating to the establishment and activity of the Folk Dance Section. It was the first state institution to collect primary and secondary research sources relating to folk dance structure and to the social context of a rural dance practice. Apart from that, it was the institution for education on folk dance preservation and staging. The focus of the paper is on the fundamental documents of ethnochoreological cultural and research policy in Serbia, manuscripts The Draft for Work at the Folk Dance Section of the Ethnographic Museum in Belgrade [Nacrt za rad u Otseku narodnih igara pri Etnografskom muzeju u Beogradu] (1939) and The Program for Work at the Department for Intangible Culture with the Sections: 1) Folk Dances and Folk Music; 2) Folk Literature; 3) Folk Art and Ornamentation; 4) Folk Customs and Religion; 5) Folk Medicine [Program rada u Odeljenju za duhovnu kulturu sa Otsecima: 1) za narodne igre i narodnu muziku; 2) za narodnu književnost; 3) za narodnu likovnu umetnost i ornamentiku; 4) za narodne običaje i veru; 5) za narodnu medicinu] (1946). The aim of this study is to contribute to the history of ethnochoreology in Serbia by introducing the ideas of Ljubica Janković concerning folk dance research and preservation strategies because of their importance for the interpretation of numerous ethnochoreological and ethnomusicological theoretical and analytical results, mostly achieved in cooperation with her sister, Danica Janković. In addition, we indicate the applicability of the first official ethnochoreological ideas for current folk dance research in Serbia. [Projekat Ministarstva nauke Republike Srbije, br. 177004: Identiteti srpske muzike od lokalnih do globalnih okvira: tradicije, promene, izazovi]